Tenidap sodium inhibits secretory non-pancreatic phospholipase A2 synthesis by foetal rat calvarial osteoblasts - W. Pruzanski; B. P. Kennedy; H. van den Bosch; E. Stefanski; M. Wloch; P. Vadas (Hindawi Limited, 1995)
Tenidap (TD) was initially defined as a dual inhibitor of cyclooxygenase and lipoxygenase. This study was designed to assess its inhibitory activity against proinflammatory phospholipase A2. This study shows that TD inhibits the synthesis of pro-inflammatory secretory non-pancreatic phospholipase A2 (sPLA2). Concentrations as low as 0.25 μg/ml (0.725 μM) reduced the release of sPLA2 by 40% from foetal rat calvarial osteoblasts stimulated with IL-1β and TNFα, whereas a concentration of 2.5 μg/ml (7.25 μM) reduced the release by over 80%. TD also markedly reduced the release of sPLA2 from unstimulated cells. There was no direct inhibition of sPLA2 enzymatic activity by TD in vitro. Northern blot analysis showed that TD did not affect the sPLA2 mRNA levels; however, immunoblotting showed a dose-dependent reduction in sPLA2 enzyme. These results, together with a marked reduction in sPLA2 enzymatic activity, suggest that TD inhibits sPLA2 synthesis at the post-transcriptional level. Therefore TD seems to inhibit the arachidonic acid cascade proximally to cyclooxygenase and lipoxygenase and its anti-inflammatory activity may be related at least in part to the inhibition of sPLA2 synthesis.